Законодавчі засади нової стратегії державної екологіічної політики України - Каракаш, Ілля Іванович; Каракаш, Илья Иванович; Karakash, Il'ja (My University, 2011)
Article is dedicated to the examination of the basic directions (Strategy) of the state ecological policy of the Ukraine to the period until 2020, which were affirmed by the law of the Ukraine dated December 21, 2010, the determining at present new directions of the state ecological policy of the country. For the purpose of the realization of strategy the national plan of actions on the protection of natural environment during the years 2011– 2015 is developed and affirmed by the government of the Ukraine.
Каракаш І. І. Законодавчі засади нової стратегії державної екологіічної політики України / І. І. Каракаш // Наукові праці Національного університету «Одеська юридична академія». Т. 10 / голов. ред. С. В. Ківалов ; МОНмолодьспорт України, НУ "ОЮА". – Одеса : Юрид. л-ра, 2011. – C. 335-344.
Keywords: державна екологічна політика; Національний план дій; государственная экологическая политика; Национальный план действий; State Environmental Policy; National Plan of Action